The effects of the changes in postmodern pedagogical paradigms on engineering education in Turkey - Sevindik, T.; Akpinar, B. (Taylor & Francis Ltd, 2007)
The aim of this research is to determine to what extent the postmodern pedagogic changes have reflected engineering education in Turkey. A total of 781 students were taken as a poll for this purpose. The findings showed that engineering education in Turkey is affected by the positivist philosophy and behaviourist approach. At these schools instruction focuses on mental development and depends on presentation of knowledge. Cooperation of school and industry is not functional. Instructors are pedagogically insufficient. The problem is rather that Turkish engineering schools are still continuing their education according to the Industrial Age, in Postmodern Information Age. These schools are far from graduating those engineers having the qualities of postmodern age. Areconstruction is inevitable.
Keywords: Postmodern pedagogy and engineering education; Turkish engineering education in students' views; Turkish engineering education, and problems